2014
DOI: 10.5539/ijef.v6n4p210
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Dividend Policy in Jordan

Abstract: This study investigates the relationship between corporate governance and dividend policy in Jordan using a sample of 47 industrial company listed in Amman Stock Exchange (ASE) during the period 2005-2011. The results show that large firms with high investment opportunity set (growth) and high return on equity make large dividend payment, but firms with high financial leverage degree make lesser dividend payment. The random regression wasused to test the relationship between the corporate governance factors (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…The studies found negative association between managerial ownership and dividend payout. The results are also in agreement with extant literature (Al-Amarneh & Yaseen, 2014;Rizqia & Aisjah, 2013;Sindhu et al, 2016). That inverse correlation exists between shares held by managers and dividend policy.…”
Section: Managerial Ownership and Decision To Pay Dividendssupporting
confidence: 91%
“…The studies found negative association between managerial ownership and dividend payout. The results are also in agreement with extant literature (Al-Amarneh & Yaseen, 2014;Rizqia & Aisjah, 2013;Sindhu et al, 2016). That inverse correlation exists between shares held by managers and dividend policy.…”
Section: Managerial Ownership and Decision To Pay Dividendssupporting
confidence: 91%
“…However, the impact of MLS on bank profitability has until now been underexplored. Most previous studies of bank ownership structure [1,2,31,32] have focused on dominant or major shareholders and demonstrate the existence of a positive relationship between ownership concentration and bank perfor-mance [6,33,34]. However, to our knowledge, the effect of MLS on bank profitability has not yet been investigated.…”
Section: The Effect Of Multiple Large Shareholders On Profitability Amentioning
confidence: 93%
“…Karena keputusan kebijakan dividen termasuk salah satu masalah agensi, maka dalam pengambilan keputusan kebijakan dividen, harus mempertimbangkan kepentingan tiap pihak. Tingkat pembayaran dividen yang tinggi dapat meminimalisasikan masalah keagenan agensi yaitu konflik antara manajer dan pemegang saham (Al-Amarneh & Yaseen, 2014).…”
Section: Karakteristik Kebijakan Dividen Dan Manajemen Labaunclassified